Functionality of Elaeocarpus serratus leaves on growth, meat quality and cost return analysis in broiler rearing - Islam, Md Manirul; Sumy, Meherunnesa Chowdhury; Adhikary, Kona; Bhowmik, Priunka (Asian Journal of Medical and Biological Research, 2021)
The study was conducted to evaluate the effects of olive leaves with probiotics (OLP) on growth performance, carcass characteristics, meat quality, blood parameters and oxidative stability of meat in broiler. A total of 160 day old, unsexed Cobb-500 chicks were distributed in to five dietary treatment groups: Control (Basal diet), OLP-1 (Basal diet + 0.4% OLP, DM basis), OLP-2 (Basal diet + 0.8% OLP, DM basis), OLP-3 (Basal diet + 1.2% OLP, DM basis) and OLP-4 (Basal diet + 1.6% OLP, DM basis) having 4 replications with 8 birds in each in a completely randomized design. Results showed that the live weight, overall average daily gain (ADG) increased significantly (p<0.05) in all treatment groups compared to control. The weekly feed conversion ratio (FCR) reduced significantly (p<0.05) in 0-14 days and the weekly ADG improved in 15-28 days. Blood cholesterol and high density lipoprotein (HDL) increased significantly (p<0.05) in all treatment groups except OLP-4 compared to control. The dressing percentage showed significant (p<0.05) difference among treatment groups and control. Organs weight were similar among treatment groups, although the breast meat and bursa weight differed significantly (p<0.05) in treatment groups. A significant increase (p<0.05) in meat crude protein (CP) and total ash content in treatment groups relative to control. Meat thiobarbituric acid reactive substances (TBARS) significantly (p<0.05) decreased at 0.8%, 1.2% and 1.8% during 1st, 2nd, 3rd weeks and in average value as well. Net return and benefit cost ratio (BCR) substantially increased in all treatment groups compared to control (p<0.05). Finally, dietary OLP supplementation improved growth performance, meat CP and ash content, increased blood cholesterol, HDL content, net rutrun and BCR while reduced meat TBARS value. Thus, olive leaf probiotics can be a potential source to be used as feed additive in broiler. Asian J. Med. Biol. Res. December 2020, 6(4): 650-658